Recruitment and selection of civil servants in Zarraga and Calinog, Iloilo, Philippines from 1998-2003 - Gamba, Ma. Theresa P.
This is a comparative study of the recruitment and selection process of civil servants in the municipalities of Zarraga and Calinog, Philippines from 1998-2001. In our study, we would like to establish the legal framework governing recruitment and selection of municipal personnel in the Philippines in general and in two concerned municipalities in particular. Furthermore, we would like to assess the process of recruitment and selection as provided by the Civil Service Commission and by the Local Government Code of 1991 with the actual practices in the municiplaties of Zarraga and Calinog., The respondents for our study were chosen through purposive Municipal personnel who were hired and or appointed to the position, be it as casual, temporary or permanent, front the period of 1998 to 2001 were considered as respondents. Also, persons concerned on the hiring and selection of municipal personnel, such as the mayor and the members of the Personnel Selection Board (PSB), were considered as respondents. Thus, in Zarraga, we have fifteen respondents and in Calinog, we have twenty-one respondents. Furthermore we have three key informants from each municipalities who were chosen based on their personal knowledge of the politics behind the recruitment and selection of personnel on their respected municipalities. Our study employed the questionnaire and the interview as the tools in gathering of data. We have two sets of questionnaire: one is for those who were hired (i.e., municipal personnel who were hired from 1998 to 2001), and the other set is for those who are hiring (i.e., the mayor and the members of the PSB). The interview was used for our key informants but it was also employed as a follow-up tool in cases where some respondents failed to answer important items in the questionnaire. Based on the data we have gathered, there are many factors involved in the process of recruitment and selection of personnel in Zarraga and Calinog, from 1998-2001. Aside from the necessary qualifications provided by the Local Government Code of 1991 and the Civil Service Law and Rules, the relationship of the hiring authorities to the applicants and the position of the recommending person matters in the applicants' chance of being recruited/or selected for the position. Some of the societal values of the respondents were brought in the organization such as "utang loob", political patronage "familism", and "pakikisama".